Police enforcement of COVID-19 rules in China and South Korea - Kutnjak Ivković, Sanja (Policing during the COVID-19 pandemic, 2024)
This chapter explores the COVID-19 police enforcement practices in China and South Korea. Whereas both countries are examples of collectivist societies in which the achievement of group-related goals is highly valuedAQ AQ: Please note that abstract should stand alone. It will not appear in the print version. This is for xml purpose only. Hence, the citation has been deleted from the abstract. Please confirm if this is fine, their approaches to dealing with the pandemic were quite different. Using the surveys of police officers from China and South Korea, collected in 2021, we study typical responses to the police officer observations of violations of COVID-19 rules. We find that Chinese police officers were more likely to say that they would react when they notice a violation of COVID-19 than the Korean officers were. The results illustrate different enforcement patterns. On the one hand, the Chinese police officers were more likely to say that they would issue a warning. On the other hand, the Korean officers were more likely to say that they would either issue a ticket or even make an arrest.